Ghrelin Gene Variants Influence on Metabolic Syndrome Components in Aged Spanish Population - Mora, Mireia (PLoS One, 2015)
BACKGROUND: The role of genetic variations within the ghrelin gene on cardiometabolic profile and nutritional status is still not clear in humans, particularly in elderly people. OBJECTIVES: We investigated six SNPs of the ghrelin gene and their relationship with metabolic syndrome (MS) components. SUBJECTS AND METHODS: 824 subjects (413 men/411 women, age 77.31±5.04) participating in the Mataró aging study (n = 310) and the Hortega study (n = 514) were analyzed. Anthropometric variables, ghrelin, lipids, glucose and blood pressure levels were measured, and distribution of SNPs -994CT (rs26312), -604GA (rs27647), -501AC (rs26802), R51Q (rs34911341), M72L (rs696217) and L90G (rs4684677) of the ghrelin gene evaluated. Genotypes were determined by multiplex PCR and SNaPshot minisequencing. MS (IDF criteria) was found in 54.9%. RESULTS: No association between any of the SNPs and levels of total fasting circulating ghrelin levels was found. C/A-A/A genotype of M72L was associated with increased risk of central obesity according to IDF criteria, while G/A-G/G genotypes of -604GA with reduced risk. A/A genotype of -501AC polymorphism was associated to decreased BMI. In relation to lipid profile, the same genotypes of -604GA were associated with increased total cholesterol and LDL-cholesterol and -501AC with reduced triglycerides. There were no associations with systolic or diastolic blood pressure levels or with hypertension, glucose levels or diabetes and ghrelin polymorphisms. However, G/G genotype of -604GA was associated with glucose >100 mg/dL. Haplotype analysis showed that only one haplotype is associated with increased risk of waist circumference and central obesity. The analysis of subjects by gender showed an important and different association of these polymorphisms regarding MS parameters. CONCLUSION: Ghrelin gene variants -604GA, -501AC and M72L are associated with certain components of MS, in particular to BMI and lipid profile in elderly Spanish subjects.